Sociodemographic and clinical factors related to the progression of disability in patients with multiple sclerosis - Aníbal Arteaga Noriega; José William Martínez; John Fredy Castro Álvarez; Dione Benjumea Bedoya; Johanna Gutiérrez Vargas; Angela Segura Cardona; Difariney González Gómez; María Isabel Zuluaga; José Zapata Berruecos (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2023)
Multiple sclerosis (MS) is a chronic inflammatory demyelinating disease of the central nervous system (CNS), with variable prognosis, and significant social impact. The prevalence in Colombia was 7.52 per 100,000 inhabitants during 2013 and has increased by 60% from 2009 to 2013. Objective: identify the sociodemographic and clinical factors related to disability progression in MS. Methodology: A descriptive study with a cross-sectional analytical component was carried out using disability progression as the dependent variable. The medical records of 216 patients living within the Metropolitan Area of Valle de Aburrá, Antioquia, Colombia. Results: In the multivariate model, by adjusting the MS phenotype for the other variables, the following factors were associated with a greater likelihood of having disability progression: primary progressive (OR 3.246, 95% CI 1.294 - 8.145, P-value = 0.012); cerebellar complications (OR 2.498, 95% CI 1.186 - 5.265, P-value = 0.016); antidepressant drugs (OR 2.336, 95% CI 1.054 - 5.176, P-value = 0.037); the presence of other neurological diseases (OR 3.392, 95% CI 1.139 - 10.102, P-value = 0.028); and active lesions on magnetic resonance imaging (OR 2.162, 95% CI 1.042 - 4.485, -P = 0.038). Those with pathologies other than cardiovascular, metabolic, mental, autoimmune, or infectious diseases had a lower likelihood of disability progression (OR 0.138, 95% CI 0.024 - 0.799, P-value = 0.028). Conclusions: The results of the present work can serve as a starting point for monitoring patients, contributing to problem-solving, and improving the quality of life for people with this disease.